{4,4′-Dimethyl-2,2′-[(2,2-dimethylpropane-1,3-diyl)bis(nitrilomethanylylidene)]diphenolato}nickel(II) monohydrate - Kargar, Hadi (International Union of Crystallography, 2011)
In the title compound, [Ni(C(21)H(24)N(2)O(2))]·H(2)O, both the complex molecule and the water molecule lie on a twofold rotation axis. The Ni(II) ion is coordinated in a distorted square-planar geometry by the tetradentate ligand. The dihedral angle between the two symmetry-related benzene rings is 47.12 (8)°. In the crystal, pairs of symmetry-related O—H⋯O hydrogen bonds form R (2) (2)(6) ring motifs. In addition, there are weak intermolecular C—H⋯O hydrogen bonds, and π–π stacking interactions with a centroid–centroid distance of 3.4760 (8) Å.